2000
DOI: 10.1053/seiz.2000.0400
|View full text |Cite
|
Sign up to set email alerts
|

Ictal and interictal SPECT findings in childhood absence epilepsy

Abstract: The purpose of this study was to investigate the informative value of single photon emission tomography (SPECT) in relation to the pathophysiological functioning of the brain during absence seizures and the origin of ictal discharges in idiopathic generalized epilepsies (IGEs). Six patients with childhood absence epilepsy (CAE) were selected for the study and two consecutive SPECT sessions were performed concomitant with EEG recordings revealing normal results and during hyperventilation (HV) studies where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 13 publications
1
20
0
1
Order By: Relevance
“…32 Recent EEG-fMRI studies of CAE and related forms of generalized epilepsy demonstrate significant BOLD signal changes during seizures in a complex network of cortical and subcortical areas. 8,10,11,13,16 Interestingly, CAE characteristically displays widespread, bilaterally synchronous SWD on EEG recordings [5][6][7]33 and bilaterally symmetric BOLD fMRI changes during seizures. [8][9][10]16 The present findings support the notion that abnormal bilateral network synchrony occurs during the interictal period as well, operating at a slower time scale, and preferentially involving the lateral orbitofrontal cortices.…”
Section: Discussionmentioning
confidence: 99%
“…32 Recent EEG-fMRI studies of CAE and related forms of generalized epilepsy demonstrate significant BOLD signal changes during seizures in a complex network of cortical and subcortical areas. 8,10,11,13,16 Interestingly, CAE characteristically displays widespread, bilaterally synchronous SWD on EEG recordings [5][6][7]33 and bilaterally symmetric BOLD fMRI changes during seizures. [8][9][10]16 The present findings support the notion that abnormal bilateral network synchrony occurs during the interictal period as well, operating at a slower time scale, and preferentially involving the lateral orbitofrontal cortices.…”
Section: Discussionmentioning
confidence: 99%
“…A fMRI study also showed significant hemodynamic changes in the bilateral thalamic and cortical areas during the generalized spike and wave or polyspike and wave bursts in IGE patients [1]. Furthermore, a 99m Tc-HMPAO SPECT study of 6 patients with childhood absence epilepsy reported a diffuse increase in cerebral blood flow including thalamus during hyperventilation [40] and an H 2 15 O PET study showed a mean global increase in blood flow during typical absence and a focal increase of thalamic blood flow following hyperventilation-induced absences with generalized spike-wave discharges [30]. These findings suggest the key role of the thalamo-cortical networks in the pathogenesis of all subsyndromes of IGE.…”
Section: Introductionmentioning
confidence: 95%
“…Human and animal studies have shown large increases in neuronal activity, CBF, and metabolism during GTCS (reviewed in . However, some investigators have shown increases in CBF during SWD (Prevett et al, 1995;Yeni et al, 2000), whereas others have shown the opposite (Bode, 1992;Nehlig et al, 1996;Sanada et al, 1988;Sperling and Skolnick, 1995).…”
mentioning
confidence: 97%